8x+5=-6x-9

Simple and best practice solution for 8x+5=-6x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+5=-6x-9 equation:


Simplifying
8x + 5 = -6x + -9

Reorder the terms:
5 + 8x = -6x + -9

Reorder the terms:
5 + 8x = -9 + -6x

Solving
5 + 8x = -9 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
5 + 8x + 6x = -9 + -6x + 6x

Combine like terms: 8x + 6x = 14x
5 + 14x = -9 + -6x + 6x

Combine like terms: -6x + 6x = 0
5 + 14x = -9 + 0
5 + 14x = -9

Add '-5' to each side of the equation.
5 + -5 + 14x = -9 + -5

Combine like terms: 5 + -5 = 0
0 + 14x = -9 + -5
14x = -9 + -5

Combine like terms: -9 + -5 = -14
14x = -14

Divide each side by '14'.
x = -1

Simplifying
x = -1

See similar equations:

| (6X-8)+10=5X+20 | | 5x+2=15x | | [-14]+[4]= | | 3x-2=4(x-2)9 | | 9x^2+47x-42=0 | | (1-4i)(1+4i)= | | 4(-6)-2(1+6)= | | -2d^22f^12/c^36= | | 45=3-(2x-7) | | 5z-2(2z+1)=19 | | 4.5+4=0.6x-3 | | -8+5=313 | | 5x+1=-(4x-7) | | y-6=1/5(x-3) | | 11x-19=5(2x+5)-6 | | 2+4lnx=5 | | 55(x+2.5)=45*x | | 3-4a(11)=41 | | -9(3s+4)= | | X-2/3=1/6 | | 4x+17=2x-7 | | (2x^2-x-1)*(5-x^2)=0 | | 12w^2+9w= | | 5w^2+2w-63=0 | | 4x^2-9-2(2x-3)+x(2x-3)=0 | | B/15-19=-6 | | 4/(6-) | | 10-1x-(-2)-8+4x= | | 2(90-x)=3(90-2x) | | (X^2-12)+(3x+6)=x | | 4z-6=6z-3z | | 6x+7-8(x+1)=5x+4 |

Equations solver categories